Measurement of (IL-11 ) Levels in Patients with Rheumatoid Arthritis (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Background:Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease that affects the joints principally. Synovitis , cartilage and bone erosion are the most prominent symptoms of (RA).  Stages of development of this disease are very complex, Synovial cells that rupture and form inflammation in the synovium, followed by cartilage and bone deterioration. Cytokines are proteins that play a crucial role in the onset arise causing and progression of the disease. This research aims to learn more about interleukin-11, which is a protein produced by the immune system. A cytokine belongs to the interleukin-6 family. It has pro- and anti-inflammatory potentials and its relationship to the disease can be determined by measuring the level of (IL-11) concentration.Materials and Methods:The current study included 45 patients with (RA), in addition to 45 (apparently healthy) subjects as a control group of the study.  These samples were collected from Marjan Hospital in Babylon Governorate (joints unit) during the period from 1/11/2021 to 3/15/2022.  The sera of all patients and control group were examined for determination of IL-11 concentration level, using enzyme-linked immunosorbent assays, which are a type of immunoassay in which the enzyme is coupled to (ELISA).Results:At the likelihood level, the study's findings have revealed a considerable decrease in IL-11 level (P≤0.05) for patients with (RA), when comparing the rates of the same criteria for the control group.Conclusion:The concentration of interleukin 11 in the sera of rheumatoid arthritis patients was found to be less than in the control group in the current investigation.